Effects of Photobiomodulation Therapy on Oxidative Stress in Muscle Injury Animal Models: A Systematic Review - Santos, Solange Almeida dos (2017)
This systematic review was performed to identify the role of photobiomodulation therapy on experimental muscle injury models linked to induce oxidative stress. EMBASE, PubMed, and CINAHL were searched for studies published from January 2006 to January 2016 in the areas of laser and oxidative stress. Any animal model using photobiomodulation therapy to modulate oxidative stress was included in analysis. Eight studies were selected from 68 original articles targeted on laser irradiation and oxidative stress. Articles were critically assessed by two independent raters with a structured tool for rating the research quality. Although the small number of studies limits conclusions, the current literature indicates that photobiomodulation therapy can be an effective short-term approach to reduce oxidative stress markers (e.g., thiobarbituric acid-reactive) and to increase antioxidant substances (e.g., catalase, glutathione peroxidase, and superoxide dismutase). However, there is a nonuniformity in the terminology used to describe the parameters and dose for low-level laser treatment.